Case Report: Trissing balloon inflation and percutaneous coronary intervention with drug-coated balloons for the treatment of restenosis of a left main trifurcation lesion - Amata, Francesco; Gioia, Francesco Paolo; Liccardo, Gaetano; Barberis, Giancarlo; Ferrante, Giuseppe (Frontiers in Cardiovascular Medicine, 2025)
We report the case of a 62-year-old male with multiple cardiovascular risk factors and comorbidities who presented to our institution due to unstable angina. One year earlier, he underwent percutaneous coronary intervention (PCI) to unprotected left main trifurcation lesion involving the ostial left anterior descending artery (LAD) (Medina classification 0-0-1-0) with provisional stenting technique with single drug-eluting stent (DES) implantation from left main to LAD and PCI to LAD with single DES implantation from LAD in crossover with D1 for the treatment of LAD-D1 bifurcation lesion (Medina 1-1-0). Coronary angiography by radial approach found sub-occlusive restenosis of both jailed ostial ramus intermediate (RI) and left circumflex (LCX), with patency of DES to left main LAD and a significant in-stent restenosis (ISR) of DES to LAD at the bifurcation with D1. LAD ISR was treated with PCI with single DES implantation with optimal angiographic results. The left main trifurcation restenosis was treated by radial approach PCI with simultaneous trissing balloon inflation to left main, RI, and LCX, followed by kissing balloon with drug-coated balloons with sirolimus elution to RI and LCX, subsequent trissing balloon inflation, and final proximal optimization technique to the left main achieving an optimal angiographic result. Planned follow-up angiography at 1 year showed persistence of optimal angiographic results.